Proton conductive battery cell structure, proton conductor, electrochemical device, and method for producing proton conductor

The existing technology is solved by using the metal oxide Bax1Srx2A1-yMyO3-δ with a perovskite structure in the proton-conducting battery cell structure and adjusting the ratio of Sr on the air electrode side and the hydrogen electrode side to form a gradient structure. The leakage current problems and high resistance caused by hole conduction achieve the balance of high ion mobility and low resistance.

CN115461900BActive Publication Date: 2025-02-14SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180031900.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-18
Filing Date
2021-05-28
Publication Date
2025-02-14
Estimated Expiration
2041-05-28

AI Technical Summary

Technical Problem

Existing proton-conducting metal oxides are prone to hole conduction in an oxygen environment, resulting in an increase in leakage current, a decrease in electromotive force, or a decrease in current efficiency during electrolysis of water vapor. At the same time, although the added strontium zirconate with yttrium showed high ion migration number, it had extremely high resistance and was not suitable for use in fuel cells.

Method used

The metal oxide Bax1Srx2A1-yMyO3-δ with a perovskite-type structure is used as the solid electrolyte layer, and the ratio of Sr is adjusted on the air electrode side and the hydrogen electrode side to form a gradient structure to take into account the high ion migration number and low resistance value.

Benefits of technology

It realizes the increase in the ion migration number while maintaining a low resistance, and is suitable for electrochemical devices such as fuel cells with high output and high ion migration number.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115461900B_ABST
    Figure CN115461900B_ABST
Patent Text Reader

Abstract

The present invention is a proton-conducting battery cell structure having an air electrode, a hydrogen electrode, and a solid electrolyte layer between the air electrode and the hydrogen electrode, wherein the solid electrolyte layer comprises at least a first solid electrolyte layer composed of a dense substance, wherein the first solid electrolyte layer comprises a metal oxide having a perovskite structure and represented by the following formula (1), wherein the ratio of Sr near the surface of the air electrode side of the first solid electrolyte layer to the total amount of Ba and Sr is 0.4 or more, and the ratio of Sr near the surface of the hydrogen electrode side of the first solid electrolyte layer to the total amount of Ba and Sr is 0.003 or more and 0.3 or less. Ba x1 Sr x2 A 1‑y M y O 3‑δ (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a proton conductive battery cell structure, a proton conductor, an electrochemical device, and a method for producing a proton conductor.

[0002] This application claims the benefit of Japanese Application No. 2020-104994, filed on June 18, 2020, and all the contents described in the Japanese Application are incorporated herein by reference. Background Art

[0003] As solid electrolytes applicable to PCFCs (Protonic Ceramic Fuel Cells) using hydrogen ions (protons) as charge carriers, proton conductive metal oxides having a perovskite structure are known (for example, Patent Documents 1 to 4).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: Japanese Patent Application Publication No. 2001-307546;

[0007] Patent Document 2: Japanese Patent Application Publication No. 2007-197315;

[0008] Patent Document 3: Japanese Patent Application Publication No. 2016-103409;

[0009] Patent document 4: Japanese Patent Application Publication No. 2016-160111. Summary of the invention

[0010] The proton conductive battery cell structure of the present invention comprises an air electrode, a hydrogen electrode, and a solid electrolyte layer interposed between the air electrode and the hydrogen electrode.

[0011] The solid electrolyte layer at least comprises a first solid electrolyte layer composed of a dense substance.

[0012] The first solid electrolyte layer includes a metal oxide having a perovskite structure and represented by the following formula (1):

[0013] Ba x1 Sr x2 A 1-y M y O 3-δ (1)

[0014] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0015] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0016] δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5),

[0017] The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) in the vicinity of the surface of the first solid electrolyte layer on the air electrode side is 0.4 or more, and

[0018] The ratio of the Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the surface on the hydrogen electrode side of the first solid electrolyte layer is 0.003 or more and 0.3 or less.

[0019] The proton conductor of the present invention is used as the first solid electrolyte layer in the proton conductive battery cell structure of the present invention.

[0020] The proton conductor is a layered material composed of a dense substance, and contains a metal oxide having a perovskite structure and represented by the following formula (1):

[0021] Ba x1 Sr x2 A 1-y M y O 3-δ (1)

[0022] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0023] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0024] δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5);

[0025] The ratio of Sr to the total amount of Ba and Sr near the first main surface (Sr / [Ba+Sr]: based on the number of atoms) is 0.4 or more, and

[0026] The ratio of the above-mentioned Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the second main surface is 0.003 or more and 0.3 or less.

[0027] The electrochemical device of the present invention includes the proton conductive battery cell structure of the present invention.

[0028] A method for producing a proton conductor of the present invention is a method for producing a proton conductor used as the first solid electrolyte layer of the proton conductive battery cell structure of the present invention.

[0029] The manufacturing method comprises the steps of bringing a mixture of a powder of a metal oxide having a perovskite structure and represented by the following formula (3) and a powder of a strontium compound into contact with the surface of the first solid electrolyte precursor layer on the air electrode side, and subjecting the mixture to a heat treatment at 1200 to 1400° C.,

[0030] Sr x2 A 1-y M y O 3-δ (3)

[0031] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0032] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0033] δ is the amount of hypoxia, satisfying 0.95≤x2≤1.10, 0<y≤0.5),

[0034] The first solid electrolyte precursor layer contains a metal oxide having a perovskite structure and represented by the following formula (2):

[0035] Ba x1 A 1-y M y O 3-δ (2)

[0036] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0037] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0038] δ is the amount of hypoxia, satisfying 0.95≤x1≤1.10, 0<y≤0.5).

[0039] Another method for producing a proton conductor of the present invention is a method for producing a proton conductor used as the solid electrolyte layer of the proton conductive battery cell structure of the present invention.

[0040] The manufacturing method comprises the steps of applying a paste containing a powder of a metal oxide having a perovskite structure and represented by the following formula (3), a powder of a strontium compound, and a binder to the surface of the first solid electrolyte precursor layer on the air electrode side, and heating the paste at 1200 to 1400° C.

[0041] Sr x2 A 1-y M y O 3-δ (3)

[0042] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0043] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0044] δ is the amount of hypoxia, satisfying 0.95≤x2≤1.10, 0<y≤0.5),

[0045] The first solid electrolyte precursor layer contains a metal oxide having a perovskite structure and represented by the following formula (2):

[0046] Ba x1 A 1-y M y O 3-δ (2)

[0047] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0048] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0049] δ is the amount of hypoxia, satisfying 0.95≤x1≤1.10, 0<y≤0.5). BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a diagram schematically showing an example of a proton conductive battery cell structure of the present invention.

[0051] Figure 2 This is a diagram schematically showing another example of the proton conductive battery cell structure of the present invention.

[0052] Figure 3A 3 is a graph showing the element ratio of Ba and Sr in the solid electrolyte layer formed in Example 1.

[0053] Figure 3B for Figure 3A A partial enlarged view of .

[0054] Figure 4A 3 is a graph showing the element ratio of Ba and Sr in the solid electrolyte layer formed in Example 2.

[0055] Figure 4B for Figure 4A A partial enlarged view of .

[0056] Figure 5 Graph showing the element ratio of Ba and Sr in the solid electrolyte layer formed in Example 3.

[0057] Figure 6Graph showing the element ratio of Ba and Sr in the solid electrolyte layer formed in Example 4.

[0058] Figure 7 3 is a graph showing the element ratio of Ba and Sr in the solid electrolyte layer formed in Comparative Example 3.

[0059] Figure 8 Graph showing the element ratio of Ba and Sr in the solid electrolyte layer formed in Comparative Example 4.

[0060] Fig. 9 This is a diagram showing an equivalent circuit of a proton conductive battery cell structure assuming hole conduction. DETAILED DESCRIPTION

[0061] [Problems to be Solved by the Invention]

[0062] Barium zirconate (BZY) doped with yttrium is a type of proton conductive metal oxide. Since it exhibits good proton conductivity even in a temperature range of 700° C. or lower, it is expected to be used as a solid electrolyte for medium-temperature fuel cells and steam electrolyzer units.

[0063] However, BZY generates hole conduction in an oxygen environment, which leads to a decrease in electromotive force due to leakage current or a decrease in current efficiency during water vapor electrolysis.

[0064] In addition, strontium zirconate (SZY) added with yttrium is also a kind of proton conductive metal oxide. Compared with BZY, SZY shows a high ion transfer number, but has extremely high resistance, which is disadvantageous for use in fuel cells.

[0065] The object of the present invention is to provide a proton conductor that can achieve both high ion transference number and low resistance value.

[0066] [Effects of the invention]

[0067] According to the present invention, a proton conductor capable of achieving both a high ion transference number and a low resistance value and a method for producing the same can be provided.

[0068] Furthermore, according to the present invention, it is possible to provide a proton conductive battery cell structure using the above-mentioned proton conductor, and an electrochemical device including the above-mentioned proton conductive battery cell structure.

[0069] [Description of Embodiments]

[0070] First, the contents of the present invention are listed and described.

[0071] (1) The proton conductive battery cell structure of the present invention comprises an air electrode, a hydrogen electrode, and a solid electrolyte layer interposed between the air electrode and the hydrogen electrode.

[0072] The solid electrolyte layer at least comprises a first solid electrolyte layer composed of a dense substance.

[0073] The first solid electrolyte layer includes a metal oxide having a perovskite structure and represented by the following formula (1):

[0074] Ba x1 Sr x2 A 1-y M y O 3-δ (1)

[0075] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0076] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0077] δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5),

[0078] The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) in the vicinity of the surface of the first solid electrolyte layer on the air electrode side is 0.4 or more, and

[0079] The ratio of the Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the surface on the hydrogen electrode side of the first solid electrolyte layer is 0.003 or more and 0.3 or less.

[0080] The proton conductive battery cell structure described in (1) above includes a solid electrolyte layer containing a metal oxide represented by the above formula (1) and wherein the content ratio of Ba and Sr is gradient from the surface on the air electrode side toward the inside of the solid electrolyte layer in a manner such that Ba increases and Sr decreases. Therefore, compared with a proton conductive battery cell structure having a solid electrolyte layer formed of BZY, the number of ion migration can be increased while maintaining a low resistance.

[0081] Therefore, the above-mentioned proton conductive battery cell structure is suitable for providing a fuel cell or the like that achieves both a high ion transfer number and a high output.

[0082] (2) In the proton conductive battery cell structure of (1) above, the ratio of the Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the center portion in the thickness direction of the first solid electrolyte layer is preferably 0.005 to 0.3.

[0083] In this case, it is more suitable to increase the ion transfer number while maintaining low resistance.

[0084] (3) In the proton conductive battery unit structure of (1) or (2) above, it is preferred that the ratio of the above Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the region of 6% of the total thickness from the surface on the air electrode side to the hydrogen electrode side in the thickness direction of the above first solid electrolyte layer is greater than 0.3.

[0085] In this case as well, it is more suitable to increase the ion transfer number while maintaining low resistance.

[0086] (4) In the proton conductive battery cell structure described in any one of (1) to (3), in the metal oxide of formula (1), 50 at% (atomic percentage) or more of element A is Zr, and element M is Y. By making element A more than half Zr, chemical stability can be improved. By making element M Y, proton conductivity can be improved.

[0087] (5) In the proton conducting battery cell structure described in any one of (1) to (3) above, the solid electrolyte layer preferably further includes a second solid electrolyte layer composed of a porous structure interposed between the first solid electrolyte layer and the air electrode.

[0088] The second solid electrolyte layer includes a metal oxide having a perovskite structure and represented by the following formula (1):

[0089] Ba x1 Sr x2 A 1-y M y O 3-δ (1)

[0090] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0091] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0092] δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5).

[0093] In this case, in the solid electrolyte layer constituting the proton conductive cell structure, the three-phase interface of the air electrode material, air, and electrolyte can be increased, thereby improving the electrode activity. Therefore, the proton conductive cell structure has a better ion transfer number.

[0094] (6) In the proton conductive battery cell structure of (5) above, preferably, in the metal oxide of formula (1), 50 at % or more of element A is Zr, and element M is Y. By making element A more than half Zr, chemical stability can be improved. By making element M Y, proton conductivity can be improved.

[0095] (7) The proton conductor of the present invention is used as the first solid electrolyte layer in the proton conductive battery cell structure of the present invention. The proton conductor is a layered material composed of a dense substance and contains a metal oxide having a perovskite structure and represented by the following formula (1):

[0096] Ba x1 Sr x2 A 1-y M y O 3-δ (1)

[0097] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0098] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0099] δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5),

[0100] The ratio of Sr to the total amount of Ba and Sr near the first main surface (Sr / [Ba+Sr]: based on the number of atoms) is 0.4 or more, and

[0101] The ratio of the above-mentioned Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the second main surface is 0.003 or more and 0.3 or less.

[0102] The proton conductor of (7) above has low resistance and a high ion transfer number.

[0103] (8) In the proton conductor of (7) above, it is preferable that the ratio of the Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the center portion in the thickness direction is 0.005 or more and 0.3 or less.

[0104] (9) The proton conductor of (7) or (8) above preferably has a ratio of the Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in a region of 6% of the total thickness from the first main surface side to the second main surface side in the thickness direction of 0.3 or more.

[0105] (10) The proton conductor described in any one of (7) to (9) above is preferably such that in the metal oxide of the formula (1), 50 at % or more of the element A is Zr, and the element M is Y.

[0106] By using the proton conductors of (7) to (10) above, it is possible to provide the proton conducting battery cell structure of the present invention.

[0107] (11) The electrochemical device of the present invention includes the proton conductive battery cell structure according to any one of (1) to (6) above.

[0108] The electrochemical device has a solid electrolyte layer having low resistance and high ion transfer number.

[0109] The electrochemical device is, for example, a fuel cell, a steam electrolysis cell unit, or a gas decomposition device.

[0110] (12) The method for producing a proton conductor of the present invention is a method for producing a proton conductor used as the first solid electrolyte layer of the proton conducting battery cell structure according to any one of (1) to (4).

[0111] The manufacturing method comprises the steps of bringing a mixture of a powder of a metal oxide having a perovskite structure and represented by the following formula (3) and a powder of a strontium compound into contact with the surface of the first solid electrolyte precursor layer on the air electrode side, and subjecting the mixture to a heat treatment at 1200 to 1400° C.,

[0112] Sr x2 A 1-y M y O 3-δ (3)

[0113] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0114] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0115] δ is the amount of hypoxia, satisfying 0.95≤x2≤1.10, 0<y≤0.5),

[0116] The first solid electrolyte precursor layer contains a metal oxide having a perovskite structure and represented by the following formula (2):

[0117] Ba x1 A 1-y M y O 3-δ (2)

[0118] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0119] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0120] δ is the amount of hypoxia, satisfying 0.95≤x1≤1.10, 0<y≤0.5).

[0121] (13) Another method for producing a proton conductor of the present invention is a method for producing a proton conductor used as the solid electrolyte layer of the proton conductive battery cell structure of (5) or (6).

[0122] The manufacturing method comprises the steps of applying a paste containing a powder of a metal oxide having a perovskite structure and represented by the following formula (3), a powder of a strontium compound, and a binder to the surface of the first solid electrolyte precursor layer on the air electrode side, and heating the paste at 1200 to 1400° C.

[0123] Sr x2 A 1-y M y O 3-δ (3)

[0124] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0125] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0126] δ is the amount of hypoxia, satisfying 0.95≤x2≤1.10, 0<y≤0.5),

[0127] The first solid electrolyte precursor layer contains a metal oxide having a perovskite structure and represented by the following formula (2):

[0128] Ba x1 A 1-y M y O 3-δ (2)

[0129] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0130] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0131] δ is the amount of hypoxia, satisfying 0.95≤x1≤1.10, 0<y≤0.5).

[0132] The proton conductor of the present invention can be produced by the above-mentioned methods for producing a proton conductor (12) and (13).

[0133] [Details of the implementation method]

[0134] Please refer to the attached Figure 1 The specific examples of the embodiments of the present invention are described below. In addition, the embodiments of the present invention are not limited to these examples. The scope of the present invention is indicated by the scope of the claims, and is intended to include all changes within the meaning and scope equivalent to the scope of the claims.

[0135] (First Embodiment)

[0136] [Proton conduction battery cell structure]

[0137] Figure 1 This is a diagram schematically showing an example of a proton conductive battery cell structure of the present invention.

[0138] The proton conductive battery cell structure 10 of the present embodiment includes an air electrode 11 , a hydrogen electrode 12 , and a solid electrolyte layer (proton conductor) 13 interposed between the air electrode 11 and the hydrogen electrode 12 .

[0139] In the proton conductive battery cell structure 10, the solid electrolyte layer 13 is sandwiched between the air electrode 11 and the hydrogen electrode 12, the first main surface 14 of the solid electrolyte layer 13 is in contact with the air electrode 11, and the second main surface 15 of the solid electrolyte layer 13 is in contact with the hydrogen electrode 12. The hydrogen electrode 12 and the solid electrolyte layer 13 are integrated by firing to form a composite of the hydrogen electrode 12 and the solid electrolyte layer 13.

[0140] The thickness of solid electrolyte layer 13 is preferably, for example, 3 μm or more and 100 μm or less, and more preferably 5 μm or more and 20 μm or less.

[0141] The thickness of the hydrogen electrode 12 is greater than that of the air electrode 11, and the hydrogen electrode 12 functions as a support for the solid electrolyte layer 13 (and further supports the proton conductive battery cell structure 10). However, the thickness of the hydrogen electrode 12 does not necessarily need to be greater than that of the air electrode 11, and for example, the thickness of the hydrogen electrode 12 and the thickness of the air electrode 11 may be of the same degree.

[0142] <Solid electrolyte layer (proton conductor)>

[0143] The solid electrolyte layer 13 is a dense layer containing a predetermined metal oxide having proton conductivity.

[0144] The above-mentioned metal oxide has a perovskite structure and is represented by the following formula (1).

[0145] Ba x1 Sr x2 A 1-y M y O 3-δ (1)

[0146] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0147] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0148] δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5).

[0149] It is preferred that 50 at% (atomic percentage) or more of the element A in the metal oxide is Zr and the element M is Y, from the perspective of providing a proton conductor with low resistance and high chemical stability. In this case, the higher the proportion of Zr in the element A, the more preferred.

[0150] The solid electrolyte layer 13 is composed of a metal oxide represented by the above formula (1), and the composition ratio of Ba and Sr is different in the thickness direction. The ratio of Sr to the total amount of Ba and Sr is higher on the air electrode 11 side than on the hydrogen electrode 12 side.

[0151] By making the ratio of Sr (and the ratio of Ba) gradient in the thickness direction of the solid electrolyte layer 13, the resistance of the solid electrolyte layer 13 can be suppressed low and the ion transfer number can be increased.

[0152] Therefore, the Ba ratio x1 and Sr ratio x2 of the metal oxide represented by the above formula (1) differ depending on the position in the solid electrolyte layer 13. The proton conductivity is improved by making the Ba ratio x1 on the hydrogen electrode 12 side higher than that on the air electrode 11 side. In addition, the ion transfer number is improved by making the Sr ratio x2 on the air electrode 11 side higher than that on the hydrogen electrode 12 side.

[0153] The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) in the vicinity of the surface of the solid electrolyte layer 13 on the air electrode 11 side is 0.4 or more.

[0154] This ensures a high ion transference number in the solid electrolyte layer 13. When the ratio of Sr on the air electrode 11 side is less than 0.4, the ion transference number is low and hole conduction is likely to occur in an oxygen environment.

[0155] The upper limit of the ratio of Sr on the air electrode 11 side is not particularly limited, and the ratio of Sr may be 1.0 or less.

[0156] The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) in the vicinity of the surface of the solid electrolyte layer 13 on the hydrogen electrode 12 side is 0.003 or more and 0.3 or less.

[0157] Thus, low resistance of the solid electrolyte layer 13 is ensured. When the ratio of Sr on the hydrogen electrode 12 side is greater than 0.3, the resistance of the solid electrolyte layer 13 becomes high. Since the proton conductivity is improved by making a small amount of Sr coexist with Ba, the resistance of the solid electrolyte layer 13 also becomes high when the ratio of Sr is less than 0.003.

[0158] From the viewpoint of reducing resistance, the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) near the surface of the solid electrolyte layer 13 on the hydrogen electrode 12 side is preferably 0.003 or more and 0.1 or less.

[0159] In the present invention, the vicinity of the surface of the solid electrolyte layer 13 refers to a position 0.5 μm inside from each of the main surfaces 14 and 15 of the solid electrolyte layer 13 in the thickness direction.

[0160] The ratio of Sr in the solid electrolyte layer 13 to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) is calculated by observing the cross section of the solid electrolyte layer 13 using a field emission electron probe microanalyzer (FE-EPMA: Field Emission-Electron Probe MicroAnalysis).

[0161] Here, a normal line was drawn to the first main surface (surface on the air electrode 11 side) 14 of the solid electrolyte layer 13, and the element amounts of Ba and Sr were measured at 0.1 μm intervals along the normal line. The ratio of Sr to the total amount of Ba and Sr was calculated from the results.

[0162] Then, a value is calculated based on the observation result at a position 0.5 μm inside in the thickness direction from the main surface of solid electrolyte layer 13 or a position closest to this position, and this value is regarded as a measured value near the surface of solid electrolyte layer 13 .

[0163] The solid electrolyte layer 13 preferably has a ratio of the Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the center portion in the thickness direction thereof of 0.005 to 0.3.

[0164] In this case, the solid electrolyte layer 13 is more suitable for suppressing the resistance to be low while increasing the ion transfer number.

[0165] On the other hand, when the Sr ratio (Sr / [Ba+Sr]) in the center portion in the thickness direction of the solid electrolyte layer 13 is less than 0.005 or greater than 0.3, the resistance of the solid electrolyte layer 13 may increase.

[0166] The center portion of the solid electrolyte layer 13 in the thickness direction refers to a position that is equidistant from the two main surfaces 14 and 15 of the solid electrolyte layer 13. In addition, a value is calculated based on the observation result at the position that is equidistant from the two main surfaces 14 and 15 of the solid electrolyte layer 13, or the position closest to the position, and the value is used as the measured value of the center portion of the solid electrolyte layer 13 in the thickness direction.

[0167] The solid electrolyte layer 13 preferably has a ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) of 0.3 or more over the entire region of 6% of the total thickness from the surface on the air electrode 11 side to the hydrogen electrode 12 side in the thickness direction.

[0168] Since the solid electrolyte layer 13 tends to have a low ion transference number on the air electrode 11 side, a high ion transference number can be ensured by satisfying the above-mentioned configuration.

[0169] The proton conductor of the present invention can ensure a high ion migration number even in an oxygen environment. The ion migration number refers to the ratio of the amount of electricity transported by anions and cations in the total amount of electricity transported by electrons, holes, anions, and cations when a current flows through an electrolyte. In addition, when the total amount of electricity transported is equal to the amount of electricity transported by anions and cations, the ion migration number is 1. For example, in the case of BZY and SZY, since protons, oxide ions, and holes exist as carriers, the ion migration number represents the ratio of the amount of electricity transported by protons and oxide ions to the total amount of electricity flowing.

[0170] <Air Electrode>

[0171] In the case of a fuel cell, for example, the air electrode 11 has a porous structure capable of adsorbing oxygen molecules and dissociating and ionizing them.

[0172] In the air electrode 11, the protons conducted through the solid electrolyte layer 13 react with the oxide ions (oxygen reduction reaction). The oxide ions are generated by dissociation of the oxidant (oxygen) introduced from the oxidant flow path.

[0173] As the material of the air electrode 11, for example, a known material used as a cathode of a fuel cell can be used. In particular, compounds containing lanthanum and having a perovskite structure (ferrite, manganite, cobaltite, etc.) are preferred, and among these compounds, compounds further containing strontium are more preferred.

[0174] Specifically, for example, lanthanum strontium cobalt iron (LSCF: La 1-x Sr x Fe 1-y Co y O 3-δ, 0<x<1, 0<y<1), lanthanum strontium manganate (LSM: La 1-x Sr x MnO 3-δ , 0<x<1), lanthanum strontium cobaltate (LSC: La 1-x Sr x CoO 3-δ , 0<x<1), etc. Here, δ represents the amount of oxygen deficiency.

[0175] The air electrode 11 can be formed by sintering the above-mentioned materials, for example.

[0176] From the viewpoint of promoting the reaction between protons and oxide ions, the air electrode 11 may also contain a catalyst such as Pt. When the catalyst is contained, the air electrode 11 can be formed by mixing the catalyst and the above-mentioned materials and sintering them. At this time, a binder, an additive, a dispersion medium, etc. may also be used together with the material of the air electrode 11 as needed.

[0177] The thickness of the air electrode 11 is not particularly limited, and may be approximately 5 μm to 40 μm.

[0178] When the proton conductive battery cell structure 10 is a steam electrolysis cell, for example, a composite of Ni and yttrium-stabilized zirconia can be used as the material of the air electrode 11 .

[0179] <Hydrogen electrode>

[0180] The hydrogen electrode 12 has a porous structure. In the case of a fuel cell, for example, a reaction (fuel oxidation reaction) occurs at the hydrogen electrode 12 in which a fuel such as hydrogen is oxidized to release protons and electrons.

[0181] As the material of the hydrogen electrode 12 , for example, a material used as an anode of a fuel cell can be used.

[0182] Specifically, nickel or a nickel compound (nickel oxide, etc.) as a catalyst component and a complex of a proton conductor can be used. In addition, the nickel compound is reduced to generate Ni during use of the battery cell structure. A metal oxide of the formula (2) described below is used as the proton conductor.

[0183] The hydrogen electrode 12 can be formed by, for example, mixing NiO powder and a powder of a metal oxide represented by the formula (2) described later, and sintering the mixture.

[0184] The thickness of the hydrogen electrode 12 may be, for example, 10 μm to 2 mm, or 10 μm to 100 μm.

[0185] The hydrogen electrode 12 may be thickened to provide a function as a support for the solid electrolyte layer 13. In this case, the thickness of the hydrogen electrode 12 may be set to, for example, 100 μm to 2 mm.

[0186] When the proton conducting battery cell structure 10 is a steam electrolysis cell, a conductive oxide that is stable in an oxidizing environment, such as lanthanum manganese oxide to which strontium is added, can be used as the material of the hydrogen electrode 12 .

[0187] [Electrochemical device]

[0188] The proton conductive battery cell structure 10 can be used as a component of an electrochemical device.

[0189] Examples of the electrochemical device include a fuel cell, a steam electrolysis cell unit, and a gas decomposition device.

[0190] <Fuel Cell>

[0191] The fuel cell may include the proton conductive cell structure 10 , and may be a fuel cell similar to a conventional fuel cell.

[0192] Specifically, for example, the following fuel cell can be cited: a separator is provided on the air electrode 11 side of the proton conductive cell structure 10 via a current collector, and the separator forms an oxidant flow path for supplying an oxidant to the air electrode 11; a separator is provided on the hydrogen electrode 12 side of the proton conductive cell structure 10 via a current collector, and the separator forms a fuel flow path for supplying fuel to the hydrogen electrode 12.

[0193] Since the fuel cell of the present invention includes the proton conductive cell structure 10 , it is possible to achieve both high output and a high ion transfer number.

[0194] The above-mentioned fuel cell can be manufactured by a known method except that the proton conductive cell structure 10 is used.

[0195] <Steam electrolysis cell unit>

[0196] The steam electrolysis cell unit may include the proton conductive cell structure 10, and other configurations may adopt known techniques. In addition, the steam electrolysis cell unit may be manufactured by a known method except for using the proton conductive cell structure 10.

[0197] <Gas decomposition device>

[0198] The gas decomposition device may include the proton conductive battery cell structure 10 .

[0199] When a gas including ammonia, methane, propane, or the like is introduced into the hydrogen electrode 12 of the proton conducting cell structure 10, a decomposition reaction of the gas occurs at the hydrogen electrode 12 to generate hydrogen. Therefore, the proton conducting cell structure 10 can be used in a gas decomposition device.

[0200] For example, hydrogen generated by decomposition of ammonia is oxidized by hydrogen electrode 12 to generate protons. The generated protons move to oxygen electrode 11 through solid electrolyte layer 13. On the other hand, N generated simultaneously by decomposition of ammonia 2 Expelled as exhaust gas.

[0201] In the gas decomposition device, the hydrogen electrode 12 may include a catalyst having a function of decomposing the gas. Examples of the catalyst having a function of decomposing a gas such as ammonia include compounds containing at least one catalyst component selected from, for example, Fe, Co, Ti, Mo, W, Mn, Ru, and Cu.

[0202] [Method for manufacturing a proton conducting battery cell structure]

[0203] The proton conductive battery cell structure 10 can be manufactured by a method including the following steps:

[0204] (1) a step of preparing an air electrode material, a solid electrolyte material A, a solid electrolyte material B, and a hydrogen electrode material (first step);

[0205] (2) After laminating the layer containing the hydrogen electrode material and the layer containing the solid electrolyte material A, the obtained laminate is heated to form a composite body in which the hydrogen electrode 12 and the solid electrolyte precursor layer are integrated (second step);

[0206] (3) a step of bringing the surface of the solid electrolyte precursor layer opposite to the hydrogen electrode 12 into contact with the solid electrolyte material B and heating it in this state to form a composite of the hydrogen electrode 12 and the solid electrolyte layer 13 (third step);

[0207] (4) A step of laminating a layer containing an air electrode material on the surface of the solid electrolyte layer 13 (the surface opposite to the hydrogen electrode side) and then heating the obtained laminate to form the air electrode 11 (fourth step).

[0208] (First process)

[0209] An air electrode material, a solid electrolyte material A, a solid electrolyte material B, and a hydrogen electrode material are prepared.

[0210] Here, as the hydrogen electrode material, a mixture of a nickel compound and a metal oxide having a perovskite structure and represented by the following formula (2) is prepared.

[0211] Ba x1 A 1-y M y O 3-δ (2)

[0212] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0213] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0214] δ is the amount of hypoxia, satisfying 0.95≤x1≤1.10, 0<y≤0.5).

[0215] The hydrogen electrode material is preferably a mixture of NiO powder and a powder of a metal oxide represented by the formula (2). The composition of the metal oxide represented by the formula (2) is preferably the same as the composition of the metal oxide represented by the formula (2) contained in the solid electrolyte material A.

[0216] As the solid electrolyte material A, a paste or slurry in which powder of the metal oxide represented by the above formula (2), a binder, and a dispersion medium are mixed is prepared.

[0217] As the above-mentioned binder, there can be mentioned known materials used in the manufacture of ceramic materials, for example, polymer binders, waxes, etc., without particular limitation. As the above-mentioned polymer binder, for example, cellulose derivatives, vinyl acetate resins, acrylic resins, etc. can be mentioned. As the above-mentioned cellulose derivative, for example, ethyl cellulose, cellulose ether, etc. can be mentioned. The concept of the above-mentioned vinyl acetate resin also includes saponified products of vinyl acetate resins such as polyvinyl alcohol. As the above-mentioned wax, for example, paraffin wax, etc. can be mentioned.

[0218] The amount of the binder is not particularly limited, and may be, for example, 1 to 20 parts by mass, and preferably 1.5 to 15 parts by mass, relative to 100 parts by mass of the powder of the metal oxide represented by the above formula (2).

[0219] Examples of the dispersion medium include water and organic solvents, but are not particularly limited. Examples of the organic solvent include hydrocarbons such as toluene, alcohols such as ethanol and isopropyl alcohol, and carbitols such as butyl carbitol acetate.

[0220] The amount of the dispersion medium is not particularly limited, and may be, for example, 50 to 200 parts by mass relative to 100 parts by mass of the powder of the metal oxide represented by the above formula (2).

[0221] The solid electrolyte material A may contain various additives such as a surfactant and a deflocculant as needed.

[0222] In the solid electrolyte material A, the composition of the metal oxide represented by the above formula (2) may be appropriately determined in consideration of the constituent elements and composition ratio of the solid electrolyte layer to be formed.

[0223] As the solid electrolyte material B, a powder of a metal oxide having a perovskite structure and represented by the following formula (3) and SrCO were prepared. 3 A mixture of powders of strontium compounds (Sr compounds).

[0224] Sr x2 A 1-y M y O 3-δ (3)

[0225] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0226] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0227] δ is the amount of hypoxia, satisfying 0.95≤x2≤1.10, 0<y≤0.5).

[0228] In the solid electrolyte material B, the composition of the metal oxide represented by the above formula (3) may be appropriately determined in consideration of the constituent elements and composition ratio of the solid electrolyte layer to be formed.

[0229] In the solid electrolyte material B, the powder of the metal oxide represented by the above formula (3) and SrCO 3 The mixing ratio of the powder of the Sr compound is preferably metal oxide: Sr compound = 99: 1 to 70: 30 on a mass basis. If the ratio of the Sr compound is too small, Sr may not be fully diffused into the solid electrolyte precursor layer. On the other hand, if the ratio of the Sr compound is too large, in the metal oxide represented by formula (1) constituting the solid electrolyte layer, x1+x2>1.1 may occur, and the chemical stability may decrease.

[0230] As the air electrode material, a paste or slurry in which powders of LSCF and LSM, which are the materials for the air electrode, are mixed with a binder and a dispersion medium is prepared.

[0231] Here, examples of the binder and the dispersion medium include the same ones as those used in the solid electrolyte material A, respectively.

[0232] The amounts of the binder and the dispersion medium are not particularly limited, and may be appropriately selected to be suitable for coating the air electrode material.

[0233] (Second process)

[0234] In the second step, a layer containing the hydrogen electrode material and a layer containing the solid electrolyte material A are stacked and heated at 1300 to 1700° C. to form a composite of the hydrogen electrode 12 and the solid electrolyte precursor layer.

[0235] In this step, the hydrogen electrode material and the solid electrolyte material A are co-sintered to form a composite.

[0236] Here, the formation method of each layer is not particularly limited, and the layer containing the hydrogen electrode material can be formed by, for example, press molding such as uniaxial molding. The layer containing the hydrogen electrode material can be pre-fired after molding and before laminating the layer containing the solid electrolyte material A. The pre-fired can be performed at a temperature lower than the temperature at which the hydrogen electrode material is sintered (for example, 900°C to 1100°C). By pre-firing, it is easy to apply the solid electrolyte material A.

[0237] The layer containing the solid electrolyte material A may be formed by applying a paste or slurry of the solid electrolyte material A to the surface of the layer containing the hydrogen electrode material by screen printing, spray coating, spin coating, dip coating or the like.

[0238] In this step, after forming the layer containing the solid electrolyte material A and before calcining, a debindering treatment for removing resin components such as a binder may be performed.

[0239] The binder removal treatment may be performed, for example, by heating at about 500° C. to 800° C. in the atmosphere.

[0240] In this step, a composite body of the hydrogen electrode 12 and the solid electrolyte precursor layer is formed in which the hydrogen electrode 12 and the solid electrolyte precursor layer are integrated.

[0241] (Third process)

[0242] In the third step, the surface of the composite solid electrolyte precursor layer opposite to the hydrogen electrode 12 is brought into contact with the solid electrolyte material B and heated in this state to form a composite of the hydrogen electrode 12 and the solid electrolyte layer 13 .

[0243] Specifically, the composite is placed on a plate made of MgO or the like with the solid electrolyte precursor layer facing upward, and the solid electrolyte material B (powder mixture) is sprinkled thereon so that the composite is buried in the solid electrolyte material B.

[0244] Then, in this state, a heat treatment is performed at 1200° C. to 1400° C. for 0 to 5 hours.

[0245] In this way, a hydrogen electrode-solid electrolyte layer composite body in which the hydrogen electrode 12 and the solid electrolyte layer 13 are integrated can be produced.

[0246] Such a method for producing a composite is also a method for producing a proton conductor of the present invention.

[0247] (Fourth process)

[0248] In the fourth step, a layer containing an air electrode material is stacked on the surface of the solid electrolyte layer 13 of the hydrogen electrode-solid electrolyte layer complex, and is heated and fired at, for example, 800° C. to 1100° C. to form the air electrode 2 .

[0249] The layer containing the air electrode material may be formed by applying a paste or slurry of the air electrode material to the surface of the solid electrolyte layer 13 by screen printing, spray coating, spin coating, dip coating, or the like.

[0250] In this step, after forming the layer containing the air electrode material and before firing, a debindering treatment for removing resin components such as a binder may be performed.

[0251] The binder removal treatment may be performed, for example, by heating at about 500° C. to 800° C. in the atmosphere.

[0252] By performing the first to fourth steps as described above, the proton conductive battery cell structure 10 can be manufactured.

[0253] Furthermore, after the third step and / or the fourth step, the side surfaces of the solid electrolyte layer may be subjected to cutting, polishing, etc. as necessary.

[0254] (Second Embodiment)

[0255] [Proton conduction battery cell structure]

[0256] Figure 2 This is a diagram schematically showing an example of a proton conductive battery cell structure of the present invention.

[0257] The proton conductive battery cell structure 20 of the present embodiment includes an air electrode 21 , a hydrogen electrode 22 , and a solid electrolyte layer (proton conductor) 23 interposed between the air electrode 21 and the hydrogen electrode 22 .

[0258] The solid electrolyte layer 23 is composed of a first solid electrolyte layer 23A and a second solid electrolyte layer 23B. The first solid electrolyte layer 23A is arranged on the hydrogen electrode 22 side and is composed of a dense material, and the second solid electrolyte layer 23B is arranged on the air electrode 21 side and is composed of a porous material.

[0259] The proton conductive battery cell structure 20 of the present embodiment is different from the proton conductive battery cell structure 10 of the first embodiment in the configuration of the solid electrolyte layer 23 .

[0260] The solid electrolyte layer 23 has a two-layer structure, and the main surface 24 of the second solid electrolyte layer 23B on the side opposite to the first solid electrolyte layer 23A is in contact with the air electrode 21, and the main surface 25 of the first solid electrolyte layer 23A on the side opposite to the second solid electrolyte layer 23B is in contact with the hydrogen electrode 22. The hydrogen electrode 22 and the solid electrolyte layer 23 are integrated by firing to form a composite of the hydrogen electrode 22 and the solid electrolyte layer 23.

[0261] The thickness of the first solid electrolyte layer 23A is, for example, preferably 3 μm or more and 100 μm or less, and more preferably 5 μm or more and 20 μm or less.

[0262] The thickness of the second solid electrolyte layer 23B is, for example, preferably 3 μm or more and 30 μm or less, and more preferably 3 μm or more and 15 μm or less.

[0263] The total thickness of the solid electrolyte layer 23 is preferably, for example, 6 μm or more and 35 μm or less.

[0264] <Solid electrolyte layer (proton conductor)>

[0265] The first solid electrolyte layer 23A is a dense layer containing a predetermined metal oxide having proton conductivity. The first solid electrolyte layer 23A can have the same structure as the solid electrolyte layer 13 in the first embodiment.

[0266] Furthermore, a preferred configuration of the first solid electrolyte layer 23A is the same as that of the solid electrolyte layer 13 in the first embodiment.

[0267] The second solid electrolyte layer 23B is a porous layer and contains a metal oxide having a perovskite structure and represented by the following formula (1).

[0268] Ba x1 Sr x2 A 1-y M y O 3-δ (1)

[0269] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0270] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0271] δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5).

[0272] In this embodiment, the solid electrolyte layer 23 has a second solid electrolyte layer 23B composed of a porous material in addition to the first solid electrolyte layer 23A. Therefore, in the solid electrolyte layer 23 (particularly the second solid electrolyte layer 23B), the three-phase interface of the air electrode material, air, and electrolyte increases, the electrode activity is improved, and the ion migration number is better.

[0273] From the viewpoint of increasing the three-phase interface among the air electrode material, air, and electrolyte and reducing the resistance, the porosity of the second solid electrolyte layer 23B is preferably 6 to 40%.

[0274] In an embodiment of the present invention, whether the solid electrolyte layer is porous or dense is determined by microscopic observation of a cross section obtained by cutting the solid electrolyte layer in the thickness direction. Specifically, the obtained microscope image is divided into pores and non-pores by binarization, and the ratio of the total area of ​​pores to the total area of ​​pores and the total area of ​​non-pores is calculated as the porosity, and the judgment is made based on the obtained porosity. In an embodiment of the present invention, the layer with a porosity of less than 5% is regarded as a dense layer, and the layer with a porosity greater than 5% is regarded as a porous layer.

[0275] The metal oxide contained in the second solid electrolyte layer 23B is preferably such that 50 at% or more of the element A in the above formula (1) is Zr, and the element M is Y. By making more than half of the element A be Zr, the chemical stability can be improved. By making the element M be Y, the proton conductivity can be improved. In this case, the higher the proportion of Zr in the element A, the more preferred.

[0276] In addition, in the metal oxide contained in the second solid electrolyte layer 23B, in the above formula (1), the ratio x1 of Ba and the ratio x2 of Sr are respectively: x1 is preferably 0≤x1≤0.6, and x2 is preferably 0.4≤x2≤1.0. The second solid electrolyte layer 23B may have the same composition as a whole, or the ratio x1 of Ba and the ratio x2 of Sr may be different depending on the position in the second solid electrolyte layer 23B.

[0277] <Air electrode / Hydrogen electrode>

[0278] The configurations of the air electrode 21 and the hydrogen electrode 22 are the same as those of the air electrode 11 and the hydrogen electrode 12 of the first embodiment.

[0279] [Electrochemical device]

[0280] The proton conductive battery cell structure 20 can be used as a component of an electrochemical device such as a fuel cell, a steam electrolysis cell unit, or a gas decomposition device, similarly to the proton conductive battery cell structure 10 of the first embodiment.

[0281] [Method for manufacturing a proton conducting battery cell structure]

[0282] The proton conductive battery cell structure 20 can be manufactured by a method including the following steps:

[0283] (1) a step of preparing an air electrode material, a solid electrolyte material A, a solid electrolyte material C, and a hydrogen electrode material (first step);

[0284] (2) After laminating the layer containing the hydrogen electrode material and the layer containing the solid electrolyte material A, the obtained laminate is heated to form a composite body in which the hydrogen electrode 22 and the solid electrolyte precursor layer are integrated (second step);

[0285] (3) a step of applying a solid electrolyte material C to the surface of the solid electrolyte precursor layer opposite to the hydrogen electrode 22 side and heating the solid electrolyte layer 23 in this state to form a composite of the hydrogen electrode 22 and the solid electrolyte layer 23 having a dense first solid electrolyte layer 23A and a porous second solid electrolyte layer 23B (third step);

[0286] (4) After laminating a layer containing an air electrode material on the surface (surface opposite to the hydrogen electrode side) of the solid electrolyte layer 23 (second solid electrolyte layer 23B), the obtained laminate is heated to form the air electrode 21 (fourth step).

[0287] (First process)

[0288] An air electrode material, a solid electrolyte material A, a solid electrolyte material C, and a hydrogen electrode material are prepared.

[0289] The air electrode material, the solid electrolyte material A, and the hydrogen electrode material are prepared in the same manner as in the first embodiment.

[0290] As the solid electrolyte material C, a mixture of a metal oxide powder having a perovskite structure and represented by the following formula (3), SrCO 3 A paste or slurry of a powder of a strontium compound (Sr compound), a binder and a dispersion medium.

[0291] Sr x2 A 1-y M y O 3-δ (3)

[0292] (wherein, element A is at least one selected from Zr, Ce and Hf,

[0293] The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc,

[0294] δ is the amount of hypoxia, satisfying 0.95≤x2≤1.10, 0<y≤0.5).

[0295] In the solid electrolyte material C, the composition of the metal oxide represented by the above formula (3) may be appropriately determined in consideration of the constituent elements and composition ratio of the solid electrolyte layer to be formed.

[0296] In the solid electrolyte material C, the powder of the metal oxide represented by the above formula (3) and SrCO 3 The mixing ratio of the powder of the Sr compound is preferably metal oxide: Sr compound = 99: 1 to 75: 25 on a mass basis. If the ratio of the Sr compound is too small, Sr may not be fully diffused into the solid electrolyte precursor layer. On the other hand, if the ratio of the Sr compound is too large, in the metal oxide represented by formula (1) constituting the solid electrolyte layer C, x1+x2>1.1 may occur, and the chemical stability may be reduced.

[0297] As the above-mentioned binder, there can be mentioned known materials used in the manufacture of ceramic materials, for example, polymer binders, waxes, etc., without particular limitation. As the above-mentioned polymer binder, for example, cellulose derivatives, vinyl acetate resins, acrylic resins, etc. can be mentioned. As the above-mentioned cellulose derivative, for example, ethyl cellulose, cellulose ether, etc. can be mentioned. The concept of the above-mentioned vinyl acetate resin also includes saponified products of vinyl acetate resins such as polyvinyl alcohol. As the above-mentioned wax, for example, paraffin wax, etc. can be mentioned.

[0298] The amount of the binder is not particularly limited, and is, for example, 1 to 20 parts by mass, preferably 1.5 to 15 parts by mass, based on 100 parts by mass of the total amount of the powder of the metal oxide represented by the formula (3) and the powder of the Sr compound.

[0299] Examples of the dispersion medium include water and organic solvents, but are not particularly limited. Examples of the organic solvent include hydrocarbons such as toluene, alcohols such as ethanol and isopropyl alcohol, and carbitols such as butyl carbitol acetate.

[0300] The amount of the dispersion medium is not particularly limited, and may be, for example, 50 to 150 parts by mass based on 100 parts by mass of the total amount of the powder of the metal oxide represented by the formula (3) and the powder of the Sr compound.

[0301] The solid electrolyte material C may further contain various additives such as a surfactant and a deflocculant as required.

[0302] (Second process)

[0303] In the second step, a layer containing the hydrogen electrode material and a layer containing the solid electrolyte material A are stacked and heated at 1300 to 1700° C. to form a composite of the hydrogen electrode 22 and the solid electrolyte precursor layer.

[0304] This step may be carried out in the same manner as the second step of the first embodiment.

[0305] (Third process)

[0306] In the third step, a paste of the solid electrolyte material C is applied to the surface of the solid electrolyte precursor layer of the composite body opposite to the hydrogen electrode 22 side and heated in this state to form a composite body of the hydrogen electrode 22 and the solid electrolyte layer 23 .

[0307] Specifically, a paste of the solid electrolyte material C is applied to the surface of the solid electrolyte precursor layer (the surface opposite to the hydrogen electrode 22 side) by screen printing, spray coating, spin coating, dip coating or the like.

[0308] Then, in this state, a heat treatment is performed at 1200° C. to 1400° C. for 0 to 5 hours.

[0309] In this way, a hydrogen electrode-solid electrolyte layer composite body in which the hydrogen electrode 22 and the solid electrolyte layer 23 are integrated can be produced.

[0310] Furthermore, by adopting the method of this step, it is possible to form the solid electrolyte layer 23 having a two-layer structure including the first solid electrolyte layer 23A composed of a dense substance and the second solid electrolyte layer 23B composed of a porous substance.

[0311] Such a method for producing a composite is also a method for producing a proton conductor of the present invention.

[0312] (Fourth process)

[0313] In the fourth step, a layer containing an air electrode material is stacked on the surface of the solid electrolyte layer 23 of the hydrogen electrode-solid electrolyte layer complex, and is heated and fired at, for example, 800° C. to 1100° C. to form the air electrode 21 .

[0314] This step may be performed in the same manner as the fourth step in the first embodiment.

[0315] By performing the first to fourth steps as described above, the proton conductive battery cell structure 20 can be manufactured.

[0316] Furthermore, after the third step and / or the fourth step, the side surfaces of the solid electrolyte layer may be subjected to cutting, polishing, etc. as necessary.

[0317] (Other embodiments)

[0318] The shape of the proton conductive battery cell structure in the first and second embodiments is a stacked type, but the shape of the battery cell structure of the present invention is not limited thereto, and may be, for example, a cylindrical shape in which the hydrogen electrode is rolled up so as to have a hollow interior.

[0319] When the proton conductive battery cell structure is in a stacked shape, the shape of each layer may be a rectangular plate or a circular plate.

[0320] Example

[0321] Next, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.

[0322] <BaZr 0.8 Y 0.2 O 2.9 Powder preparation>

[0323] Barium carbonate, zirconium oxide and yttrium oxide were added to a ball mill at a molar ratio of 1.0 for Ba and 0.2 for Y, and mixed for 24 hours to obtain a mixture. The obtained mixture was pre-calcined at 1000°C for 10 hours. The pre-calcined mixture was treated with a ball mill for 10 hours, uniaxially formed, and then fired at 1300°C for 10 hours in an atmospheric environment. The fired sample was crushed with a mortar and treated with a ball mill for 10 hours. The obtained powder was uniaxially formed again, then fired at 1300°C for 10 hours, and treated with a ball mill for 10 hours to obtain BaZr 0.8 Y 0.2 O 2.9 Powder (hereinafter also referred to as BZY20 powder).

[0324] <SrZr 0.85 Y 0.15 O 2.975 Powder preparation>

[0325] Strontium carbonate, zirconium oxide and yttrium oxide were added to a ball mill at a molar ratio of Sr to 1.0 and Y to 0.15, and mixed for 24 hours to obtain a mixture. The obtained mixture was pre-calcined at 1000°C for 10 hours. The pre-calcined mixture was treated with a ball mill for 10 hours, uniaxially formed, and then fired at 1300°C for 10 hours in an atmospheric environment. The fired sample was crushed with a mortar and treated with a ball mill for 10 hours. The obtained powder was uniaxially formed again, then fired at 1300°C for 10 hours, and treated with a ball mill for 10 hours to obtain SrZr 0.85 Y 0.15 O 2.975 Powder (hereinafter also referred to as SZY15 powder).

[0326] <Example 1>

[0327] (1) NiO and BZY20 powders were mixed in a mass ratio of 7:3, ball-milled, and then uniaxially molded. The obtained molded body was pre-fired at 1000°C, and BZY20 paste was laminated on the pre-fired molded body by screen printing. The BZY20 paste was a mixture of BZY20 powder, an organic solvent (butyl carbitol acetate (BCA)), and a binder (ethyl cellulose), and the organic solvent (butyl carbitol acetate (BCA)) was 125 parts by mass and the binder (ethyl cellulose) was 5 parts by mass relative to 100 parts by mass of the BZY20 powder.

[0328] The obtained laminated body was subjected to a binder removal treatment by heating at 750° C., and then co-sintered at 1450° C. to form a sintered body.

[0329] (2) The obtained sintered body was placed on a MgO plate with the side on which the BZY20 paste was laminated facing upward, and a mixture of SZY15 powder and SrCO was sprinkled on the sintered body. 3 The powder was mixed at a ratio of 9:1 (mass ratio) and the sintered body was embedded in the powder, and in this state, a heat treatment was performed in a heating furnace at 1300°C for 0 hours. Here, the heat treatment at 1300°C for 0 hours refers to a heat treatment in which the temperature in the furnace is raised from 20°C to 1300°C over 6 hours and 40 minutes, and after reaching 1300°C, the temperature is immediately lowered from 1300°C to 20°C over 6 hours and 40 minutes (heat treatment mode 1).

[0330] Through such steps, a hydrogen electrode-solid electrolyte layer complex A in which a disk-shaped hydrogen electrode and a solid electrolyte layer are integrated is produced.

[0331] The thickness of the solid electrolyte layer formed in this embodiment is 15 μm.

[0332] <Example 2>

[0333] First, a sintered body was formed in the same manner as in step (1) of Example 1.

[0334] Then, the sintered body was placed on a MgO plate with the side on which the BZY20 paste was laminated facing upward, and a mixture of SZY15 powder and SrCO was sprinkled thereon. 3The powder was mixed at a ratio of 9:1 (mass ratio) and the sintered body was embedded in the powder, and in this state, heat treatment was performed at 1300°C for 2 hours in a heating furnace. Here, the heat treatment at 1300°C for 2 hours refers to a heat treatment in which the temperature in the furnace is raised from 20°C to 1300°C over 6 hours and 40 minutes, then the temperature in the furnace is maintained at 1300°C for 2 hours, and then the temperature is lowered from 1300°C to 20°C over 6 hours and 40 minutes (heat treatment mode 2).

[0335] After the above heat treatment, a hydrogen electrode-solid electrolyte layer complex B is produced.

[0336] The thickness of the solid electrolyte layer formed in this embodiment is 14 μm.

[0337] <Example 3>

[0338] First, a sintered body was formed in the same manner as in step (1) of Example 1.

[0339] Then, the sintered body was placed on a MgO plate with the side on which the BZY20 paste was laminated facing upward, and SZY15 powder and SrCO were sprinkled thereon. 3 The powders were mixed at a ratio of 9:1 (mass ratio) and the sintered body was embedded in the powders, and heat treatment was performed at 1400°C for 2 hours in a heating furnace in this state. Here, the heat treatment at 1400°C for 2 hours refers to a heat treatment in which the temperature in the furnace is raised from 20°C to 1400°C over 7 hours and 27 minutes, then the temperature in the furnace is maintained at 1400°C for 2 hours, and then the temperature is lowered from 1400°C to 20°C over 7 hours and 27 minutes (heat treatment mode 3).

[0340] After the above heat treatment, a hydrogen electrode-solid electrolyte layer composite C is produced.

[0341] The thickness of the solid electrolyte layer formed in this example is 17 μm.

[0342] <Example 4>

[0343] First, a sintered body was formed in the same manner as in step (1) of Example 1.

[0344] Next, the following paste was laminated by screen printing on the surface of the obtained sintered body on which the BZY20 paste was laminated: SZY15 powder and SrCO 3 The powders were mixed at a mass ratio of 9:1, and the total amount of SZY15 powder and SrCO was 100 parts by mass. 3 The powder was mixed with 5 parts by mass of a binder (ethyl cellulose) and 130 parts by mass of an organic solvent (butyl carbitol acetate (BCA)), and then heat-treated in a heating furnace at 1300° C. for 0 hours (heat-treatment mode 1).

[0345] Through such heat treatment, a hydrogen electrode-solid electrolyte layer complex D is produced.

[0346] The thickness of the solid electrolyte layer formed in this embodiment is: the thickness of the first solid electrolyte layer composed of a dense substance is 14 μm, and the thickness of the second solid electrolyte layer composed of a porous substance is 10 μm.

[0347] Furthermore, the porosity of the first solid electrolyte layer was 0%, and the porosity of the second solid electrolyte layer was 8%.

[0348] <Comparative Example 1>

[0349] The sintered body produced in the same manner as in step (1) of Example 1 was used as the hydrogen electrode-solid electrolyte layer composite E of this comparative example.

[0350] The thickness of the solid electrolyte layer formed in this comparative example was 16 μm.

[0351] <Comparative Example 2>

[0352] NiO and SZY15 powders were mixed in a mass ratio of 7:3, ball-milled, and then uniaxially molded. The obtained molded body was pre-fired at 1000°C, and SZY15 paste was laminated on the pre-fired molded body by screen printing. The SZY15 paste was a mixture of SZY15 powder, an organic solvent (butyl carbitol acetate (BCA)) and a binder (ethyl cellulose), and the organic solvent (butyl carbitol acetate (BCA)) was 140 parts by mass and the binder (ethyl cellulose) was 5 parts by mass relative to 100 parts by mass of SZY15 powder.

[0353] The obtained laminated body was subjected to a binder removal treatment by heating at 750° C., and then co-sintered at 1450° C. to form a sintered body.

[0354] This sintered body was used as a hydrogen electrode-solid electrolyte layer composite F of this comparative example.

[0355] The thickness of the solid electrolyte layer formed in this comparative example was 15 μm.

[0356] <Comparative Example 3>

[0357] NiO and BZY20 powders were mixed at a mass ratio of 7:3, ball-milled, and uniaxially molded. The resulting molded body was pre-fired at 1000°C, and the same SZY15 paste as in Comparative Example 2 was layered on the pre-fired molded body by screen printing.

[0358] The obtained laminated body was subjected to a binder removal treatment by heating at 750° C., and then co-sintered at 1450° C. to form a sintered body.

[0359] This sintered body was used as the hydrogen electrode-solid electrolyte layer composite body G of this comparative example.

[0360] The thickness of the solid electrolyte layer formed in this comparative example was 15 μm.

[0361] <Comparative Example 4>

[0362] First, a sintered body was formed in the same manner as in step (1) of Example 1.

[0363] Then, a 500 nm thick SZY15 film was laminated on the side of the obtained sintered body on which the BZY20 paste was laminated by pulsed laser deposition (PLD).

[0364] Through such a SZY15 film forming step, the hydrogen electrode-solid electrolyte layer complex H is produced.

[0365] The thickness of the solid electrolyte layer formed in this comparative example was 15.5 μm.

[0366] <Cross-section observation and composition analysis>

[0367] Regarding the composition of the solid electrolyte layer in the hydrogen electrode-solid electrolyte layer composites prepared in Examples 1 to 4 and Comparative Examples 3 and 4, the cross-section of the solid electrolyte layer was observed and measured by a field emission electron probe microanalyzer (FE-EPMA), and "Ba / (Ba+Sr): based on the number of atoms" and "Sr / (Ba+Sr): based on the number of atoms" were calculated as the element ratios of the solid electrolyte layer. The results are shown in Tables 1 and Figure 3A , Figure 3B , Figure 4A , Figure 4B , Figure 5 , Figure 6 , Figure 7 and Figure 8 .exist Figure 3A to Figure 8 In the graph, the horizontal axis represents the position in the thickness direction of the cross section of the solid electrolyte layer, and the vertical axis represents the above-mentioned element ratio of the solid electrolyte layer.

[0368] Here, the solid electrolyte layer as the observation sample was embedded in resin and polished, carbon was vapor-deposited on the entire sample, and then cross-section processing was performed using a cross-section polisher (SM-09010) manufactured by JEOL Ltd.

[0369] As EPMA, JXA-8530F manufactured by JEOL Ltd. (JEOL) was used, and the measurement was carried out under the following conditions:

[0370] Accelerating voltage: 15 kV

[0371] Irradiation current: 100nA

[0372] Sampling time: 1s

[0373] Probe diameter: 0.1μmφ

[0374] Injection: 0.1μm.

[0375] At this time, the ZAF method was used for quantification, using BaF 2 As a standard sample of Ba, SrTiO 3 As the standard sample of Sr (all are standard samples manufactured by JEOL).

[0376] [Table 1]

[0377]

[0378] As shown in Table 1 and Figure 3A to Figure 8 As shown, in the hydrogen electrode-solid electrolyte layer complexes A to D produced in Examples 1 to 4, near the surface of the first solid electrolyte layer on the opposite side to the hydrogen electrode (also called the air electrode side), Sr / (Ba+Sr) is greater than 0.4, and a composition gradient of Ba and Sr is formed in the solid electrolyte layer.

[0379] The solid electrolyte layer in Examples 1 to 3 had a porosity of 0%, and the solid electrolyte layer in Example 4 had a porosity of 8% in a 10 μm region on the opposite side to the hydrogen electrode side (air electrode side).

[0380] On the other hand, in the hydrogen electrode-solid electrolyte layer composite G prepared in Comparative Example 3, Sr diffuses in the electrolyte layer, and the gradient formed by Sr in the composition becomes gentle. On the opposite side of the solid electrolyte layer to the hydrogen electrode (air electrode side), Sr / (Ba+Sr) is about 0.4, on the hydrogen electrode side of the solid electrolyte layer, Sr / (Ba+Sr) is about 0.3, and Sr / (Ba+Sr) is about 0.3 to 0.4 in the entire solid electrolyte layer.

[0381] In the hydrogen electrode-solid electrolyte layer composite H produced in Comparative Example 4, Sr was not detected in a region of the solid electrolyte layer that was more than 1.0 μm away from the side opposite to the hydrogen electrode.

[0382] <Electrochemical measurement and evaluation>

[0383] Fuel cells were prepared using the hydrogen electrode-solid electrolyte layer composites A to H prepared in the examples and comparative examples, and electrochemical measurements were performed using the obtained fuel cells.

[0384] (1) Production of fuel cells

[0385] As the air electrode material, a mixture of LSCF (La 0.6 Sr 0.4 Fe 0.8 Co 0.2 O 3-δ ) powder, solvent (butyl carbitol acetate) and binder (ethyl cellulose) LSCF paste. The LSCF paste is applied to the surface of the solid electrolyte layer of the hydrogen electrode-solid electrolyte layer complex by screen printing. Then, a heat treatment is performed at 1000°C for 2 hours to sinter the LSCF to form a cathode (air electrode) with a thickness of 10μm, thereby obtaining a battery cell structure.

[0386] A platinum mesh to which a lead wire was welded was attached to the surface of each of the air electrode and the hydrogen electrode of the obtained cell structure (φ16 mm) using a platinum electrode paste.

[0387] The ends of the lead wires on the opposite side to the battery cell structure are connected to a measuring device so that the current value and the voltage value between the lead wires can be measured.

[0388] (2) Output density measurement

[0389] The operating temperature was set at 600°C and hydrogen as fuel gas was added at a rate of 100 cm 3 / min into the hydrogen electrode of the fuel cell, and the air was blown at 200cm 3 / min flowed into the air electrode. The air and hydrogen were humidified to a dew point of 25°C. The voltage was measured while changing the current density, and the maximum output density was obtained from the current density and voltage. The results are shown in Table 2.

[0390] (3) Measurement of DC resistance change

[0391] Calculate the DC resistance R in the open circuit state OCV The DC resistance R when OCV-0.2V voltage is applied 0.2 R OCV / R 0.2 As an indicator of the ion transfer number.

[0392] Each DC resistance was measured by electrochemical impedance spectroscopy, and an open circuit voltage value (OCV) was also obtained at this time.

[0393] As the measuring device, a 1260A impedance / gain-phase analyzer and a 1287A potentiostat made by Solartron were used. The amplitude was ±10 mV relative to OCV or OCV-0.2 V, and the voltage was measured from 10 6The current value was swept from 0.1 Hz to 0.1 Hz, and the real part of the frequency response of the current value during the sweep was plotted as the horizontal axis and the imaginary part as the vertical axis to obtain a Nyquist plot, and the intersection with the horizontal axis was read as the DC resistance. The results are shown in Table 2.

[0394] In this evaluation, “R OCV / R 0.2 " is used as an indicator of the ion migration number. The reason is as follows.

[0395] The equivalent circuit of the proton-conducting battery cell structure with hole conduction can be shown as Fig. 9 As shown. Fig. 9 Middle, R H is the resistance of proton conduction, R h is the resistance of hole conduction, R c is the resistance of the air electrode (cathode), R a is the resistance of the hydrogen electrode (anode), and R is the total resistance.

[0396] Here, the conductivity σ and the ion transfer number t of the proton conductor can be expressed as Mathematical Formula 1:

[0397] [Mathematical formula 1]

[0398]

[0399]

[0400] In the high-frequency side slice of the impedance measurement, both Rc and Ra can be regarded as 0. Therefore, the total resistance (DC resistance) R of the proton conduction battery cell structure can be expressed as Mathematical Formula 2:

[0401] [Mathematical formula 2]

[0402]

[0403] According to the non-patent document: T.Onishi and T.Uda, Electrochemistry, 87(3), 162-174(2019), it is clear that the greater the voltage applied to the battery cell structure, the greater the hole conductivity of the battery cell structure, so the hole conductivity of the voltage applied to the power generation side is smaller than that in the open circuit state. When based on the disclosure of this document, the hole conductivity in the OCV-0.2V state is about 1 / 5 of the hole conductivity in the open circuit state. Therefore, the resistance of hole conduction in the OCV-0.2V state is about 5 times the resistance of hole conduction in the OCV state.

[0404] Here, the DC resistance in the OCV state is taken as R OCV, the DC resistance at OCV-0.2V is taken as R 0.2 , when it is the following mathematical formula 3,

[0405] [Mathematical formula 3]

[0406]

[0407] The above R 0.2 It is expressed as mathematical formula 4:

[0408] [Formula 4]

[0409]

[0410] Moreover, R OCV Relative to R 0.2 The ratio is expressed as mathematical formula 5:

[0411] [Formula 5]

[0412]

[0413]

[0414] This can fully understand the relationship between the ion migration number t and R in the open circuit state. OCV / R 0.2 Therefore, in this evaluation, R was used as described above. OCV / R 0.2 As an indicator of the ion transfer number.

[0415] [Table 2]

[0416]

[0417] Compared with the fuel cells of the hydrogen electrode-solid electrolyte layer complex evaluated in Comparative Examples 1, 3, and 4, the fuel cells of the hydrogen electrode-solid electrolyte layer complex evaluated in Examples 1 to 4 have a high migration number index, and the electrochemical device of the present invention has a good ion migration number while maintaining a high output density.

[0418] On the other hand, the fuel cells in which the hydrogen electrode-solid electrolyte layer composites of Comparative Examples 1, 3, and 4 were evaluated did not easily increase the ion transference number.

[0419] The fuel cell in which the hydrogen electrode-solid electrolyte layer composite of Comparative Example 2 was evaluated had a high transfer number index, but an extremely low output density.

[0420] As is apparent from the above, according to the present invention, it is possible to achieve both a high ion transference number and a high output.

[0421] Description of Reference Numerals

[0422] 10, 20 Battery cell structure

[0423] 11.21 Air electrode

[0424] 12.22 Hydrogen electrode

[0425] 13.23 Solid electrolyte layer

[0426] 14, 24 (First) Main Surface

[0427] 15, 25 (Second) Main Surface

[0428] 23A First solid electrolyte layer

[0429] 23B Second solid electrolyte layer

Claims

1. A proton conductive battery cell structure comprising an air electrode, a hydrogen electrode, and a solid electrolyte layer interposed between the air electrode and the hydrogen electrode, The solid electrolyte layer comprises at least a first solid electrolyte layer composed of a dense substance, The first solid electrolyte layer includes a metal oxide having a perovskite structure and represented by the following formula (1), Ba x1 Sr x2 A 1-y M y O 3-δ (1) In the formula, element A is at least one selected from Zr, Ce and Hf, The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc, δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5, The ratio Sr / (Ba+Sr) of the Sr amount in the vicinity of the surface of the air electrode side of the first solid electrolyte layer to the total amount of Ba and Sr is 0.4 or more based on the number of atoms, and The ratio Sr / (Ba+Sr) of the Sr to the total amount of Ba and Sr in the vicinity of the surface on the hydrogen electrode side of the first solid electrolyte layer is 0.003 or more and 0.3 or less.

2. The proton conductive battery cell structure according to claim 1, wherein: A ratio Sr / (Ba+Sr) of the Sr to the total amount of Ba and Sr in the center portion in the thickness direction of the first solid electrolyte layer is 0.005 or more and 0.3 or less.

3. The proton conductive battery cell structure according to claim 1 or claim 2, wherein: In the first solid electrolyte layer, a ratio Sr / (Ba+Sr) of Sr to a total amount of Ba and Sr in a region of 6% of the total thickness from the surface on the air electrode side to the hydrogen electrode side in the thickness direction is 0.3 or more.

4. The proton conductive battery cell structure according to any one of claims 1 to 3, wherein: In the above formula (1), 50 at % or more of the element A is Zr, and the element M is Y.

5. The proton conductive battery cell structure according to any one of claims 1 to 3, wherein: The solid electrolyte layer further includes a second solid electrolyte layer composed of a porous substance interposed between the first solid electrolyte layer and the air electrode. The second solid electrolyte layer includes a metal oxide having a perovskite structure and represented by the following formula (1), Ba x1 Sr x2 A 1-y M y O 3-δ (1) In the formula, element A is at least one selected from Zr, Ce and Hf, The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc, δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.

5.

6. The proton conductive battery cell structure according to claim 5, wherein: In the above formula (1), 50 at % or more of the element A is Zr, and the element M is Y.

7. A proton conductor used as the first solid electrolyte layer in the proton conductive battery cell structure according to claim 1, The proton conductor is a layered material composed of a dense substance, and contains a metal oxide having a perovskite structure and represented by the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) In the formula, element A is at least one selected from Zr, Ce and Hf, The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc, δ is the amount of hypoxia, satisfying 0.95≤x1+x2≤1.10, 0<y≤0.5, The ratio Sr / (Ba+Sr) of the amount of Sr in the vicinity of the first principal surface to the total amount of Ba and Sr is 0.4 or more based on the number of atoms, and The ratio Sr / (Ba+Sr) of the Sr to the total amount of Ba and Sr in the vicinity of the second main surface is 0.003 or more and 0.3 or less.

8. The proton conductor according to claim 7, wherein The ratio Sr / (Ba+Sr) of the Sr to the total amount of Ba and Sr in the center portion in the thickness direction is 0.005 or more and 0.3 or less.

9. The proton conductor according to claim 7 or claim 8, wherein: In the thickness direction, a ratio Sr / (Ba+Sr) of the Sr to the total amount of Ba and Sr in a region accounting for 6% of the total thickness from the first main surface side to the second main surface side is 0.3 or more.

10. The proton conductor according to any one of claims 7 to 9, wherein In the above formula (1), 50 at % or more of the element A is Zr, and the element M is Y. 11 . An electrochemical device comprising the proton conductive battery cell structure according to claim 1 .

12. A method for producing a proton conductor, the proton conductor being used as the first solid electrolyte layer of the proton conducting battery cell structure according to any one of claims 1 to 4, The manufacturing method comprises: A step of bringing a mixture of a powder of a metal oxide having a perovskite structure and represented by the following formula (3) and a powder of a strontium compound into contact with the surface of the first solid electrolyte precursor layer on the air electrode side and subjecting the mixture to a heat treatment at 1200 to 1400° C., Sr. x2 A 1-y M y O 3-δ (3) In the formula, element A is at least one selected from Zr, Ce and Hf, The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc, δ is the amount of hypoxia, which satisfies 0.95≤x2≤1.10, 0<y≤0.5, The first solid electrolyte precursor layer includes a metal oxide having a perovskite structure and represented by the following formula (2), Ba x1 A 1-y M y O 3-δ (2) In the formula, element A is at least one selected from Zr, Ce and Hf, The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc, δ is the amount of hypoxia, satisfying 0.95≤x1≤1.10, 0<y≤0.

5.

13. A method for producing a proton conductor used as the solid electrolyte layer of the proton conducting battery cell structure according to claim 5 or claim 6, The manufacturing method comprises: A process of applying a paste containing a powder of a metal oxide having a perovskite structure and represented by the following formula (3), a powder of a strontium compound, and a binder to the surface of the first solid electrolyte precursor layer on the air electrode side, and then heating the paste at 1200 to 1400° C. Sr. x2 A 1-y M y O 3-δ (3) In the formula, element A is at least one selected from Zr, Ce and Hf, The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc, δ is the amount of hypoxia, which satisfies 0.95≤x2≤1.10, 0<y≤0.5, The first solid electrolyte precursor layer includes a metal oxide having a perovskite structure and represented by the following formula (2), Ba x1 A 1-y M y O 3-δ (2) In the formula, element A is at least one selected from Zr, Ce and Hf, The element M is at least one selected from Y, Yb, Er, Ho, Tm, Gd, In and Sc, δ is the amount of hypoxia, satisfying 0.95≤x1≤1.10, 0<y≤0.5.

Citation Information

Patent Citations

  • Ionic conductor

    JP2001307546A

  • Mixed ion conductor and device using the same

    JP2007197315A

  • Method for producing ceramic, capacitor, solid oxide type fuel cell, water electrolytic device and hydrogen pump

    JP2016160111A

  • Sheet pressing device and image formation system having the same

    JP2020104994A

  • Solid oxide fuel battery

    JP2016103409A